Biochemical studies in experimental aspergillosis in goats : Tissue lipids, plasma - MANDAL, P C (The Indian Journal of Animal Sciences, 2013)
Biochemical changes in tissue and plasma lipids. plasma total protein and total immunoglobulin were studied in 25 goats during experimental aspergillosis. They were inoculated. with 5 ml spores of Aspergillus fumigatus intravenously(i/v, 7 goats), intratracheally (ilt, 10 goats) arlo intramaminarily (i/m. 8 lactating goats). Six control goats (2 in each group) were similarly inoculated with 5 ml sterile phosphate butTered saline(PBS. pH 7.4) in their respective routes. Generalised along with pulmonary aspergillosis, pulmonary aspergillosis and mycotic mastitis in the right udder halves only developed in i/v, i/t and i/m groups respectively. All goats ofi/v group died between I and II days post-inoculation (DPI) and 2 goats each were killed at different intervals in i/t and i/m groups. There was gradual and moderate decrease of total lipid. total phospholipids. total cholesterol and total free fatty acids and ncrease of total glycerides in the lungs, kidneys, liver. heart and brain of i/v group. Similar but lesser decrease of lipid componentswere observed’in the lungs of ilt group and in the udder of i/m group. The other tissues of ilt and ilm groups did not show much variation in lipid constituents. There was mild but insigniticant decrease of total lipids and its constituents in the plasma of 3 groups of goats. Total plasma protein in all the 3 groups showed negligible changes during the days of the experiment. Total irrimunoglobulin in the plasma of goats increased graduully and signiticantly on the 6 DPI in i/v group and on 23 and 30 DPI in i/t group and showed no sigriticant changes in i/m group.